2020
DOI: 10.1515/nanoph-2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in graphene and black phosphorus nonlinear plasmonics

Abstract: Abstract Over the past decade, the plasmonics of graphene and black phosphorus (BP) were widely recognized as promising media for establishing linear and nonlinear light-matter interactions. Compared to the conventional metals, they support significant light-matter interaction of high efficiency and show undispersed optical properties. Furthermore, in contrast to the conventional metals, the plasmonic properties of graphene and BP structure can be tuned by electrical and chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 214 publications
0
17
0
Order By: Relevance
“…The carrier dynamic of a saturable structure plays an important role to determine how a short pulse can be produced in large-scale vertical bilayer junctions [23]. Let us assume that the incident field is ultrashort pulse here [43]. The short pulse with two different central frequencies ω 2 and ω 3 can be written as E(r,t) = E(r)exp(−(t − t 0 ) 2 /(t d 2)) (e −iω2t + e −iω3t ), where delay of time is t 0 and t d is 200 fs.…”
Section: Tuning Quality Factor and Lifetime Of Gspmentioning
confidence: 99%
“…The carrier dynamic of a saturable structure plays an important role to determine how a short pulse can be produced in large-scale vertical bilayer junctions [23]. Let us assume that the incident field is ultrashort pulse here [43]. The short pulse with two different central frequencies ω 2 and ω 3 can be written as E(r,t) = E(r)exp(−(t − t 0 ) 2 /(t d 2)) (e −iω2t + e −iω3t ), where delay of time is t 0 and t d is 200 fs.…”
Section: Tuning Quality Factor and Lifetime Of Gspmentioning
confidence: 99%
“…Eventually, extensive research has been also recently devoted to investigate non-linear effects in graphene related 2D materials [241]. For example, BP displays a strong mid-IR saturable absorption, driven by carrier dynamics faster than those observed in graphene [242], however, no demonstration of nonlinear THz response has been observed to date, except for graphene.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…The outstanding experimental results have indicated that LDMs exhibit extraordinarily large nonlinear susceptibilities, implying a huge potential of these materials for various applications such as wavelength conversion, and ultrafast pulse characterization. [32][33][34] There have been a few reviews on the nonlinear optical properties of LDMs containing harmonic generations as a section. [16,34,35] There are also a few recent papers providing more focused discussion on the SHG in 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…The outstanding experimental results have indicated that LDMs exhibit extraordinarily large nonlinear susceptibilities, implying a huge potential of these materials for various applications such as wavelength conversion, and ultrafast pulse characterization. [ 32–34 ]…”
Section: Introductionmentioning
confidence: 99%